Synthesis of blue-luminescent seven-membered phosphorus heterocycles - Regulska, Elzbieta; Ruppert, Heiko; Rominger, Frank; Romero-Nieto, Carlos (The journal of organic chemistry, 2020)
A facile synthetic procedure to prepare π-extended seven-membered phosphorus heterocycles, both symmetric and asymmetric, is reported. The prepared molecules present a persistent nonplanar framework and are soluble in a wide variety of solvents. The seven-membered phosphorus heterocycles can be electrochemically reduced and oxidized, and photoluminesce with a blue color.
December 18, 2019
Gesehen am 24.06.2020